Betaine and Carnitine Derivatives as Herbicidal Ionic Liquids. Issue 34 (4th July 2016) - Pernak, Juliusz; Niemczak, Michał; Chrzanowski, Łukasz; Ławniczak, Łukasz; Fochtman, Przemysław; Marcinkowska, Katarzyna; Praczyk, Tadeusz
Abstract: This study focused on the synthesis and subsequent characterization of herbicidal ionic liquids based on betaine and carnitine, two derivatives of amino acids, which were used as cations. Four commonly used herbicides (2, 4‐D, MCPA, MCPP and Dicamba) were used as anions in simple (single anion) and oligomeric (two anions) salts. The obtained salts were subjected to analyzes regarding physicochemical properties (density, viscosity, refractive index, thermal decomposition profiles and solubility) as well as evaluation of their herbicidal activity under greenhouse and field conditions, toxicity towards rats and biodegradability. The obtained results suggest that the synthesized herbicidal ionic liquids displayed low toxicity (classified as category 4 compounds) and showed similar or improved efficacy against weed compared to reference herbicides. The highest increase was observed during field trials for salts containing 2, 4‐D as the anion, which also exhibited the highest biodegradability (>75 %). Abstract : The HILs are alive : New herbicidal ionic liquids (HILs) based on betaine and carnitine were synthesized and characterized in terms of physicochemical properties, herbicidal activity, and environmental impact. Depending on the type of herbicide used as the anion, the obtained salts exhibited enhanced weed control efficacy, high susceptibility to biodegradation and low toxicity.